A Molecular Mechanism for the Heparan Sulfate Dependence of Slit-Robo Signaling - Hussain, Sadaf-Ahmahni (2006)
Slit is a large secreted protein that provides important guidance cues in the developing nervous system and in other organs. Signaling by Slit requires two receptors, Robo transmembrane proteins and heparan sulfate (HS) proteoglycans. How HS controls Slit-Robo signaling is unclear. Here we show that the second leucine-rich repeat domain (D2) of Slit, which mediates binding to Robo receptors, also contains a functionally important binding site for heparin, a highly sulfated variant of HS. Heparin markedly enhances the affinity of the Slit-Robo interaction in a solid-phase binding assay. Analytical gel filtration chromatography demonstrates that Slit D2 associates with a soluble Robo fragment and a heparin-derived oligosaccharide to form a ternary complex. Retinal growth cone collapse triggered by Slit D2 requires cell surface HS or exogenously added heparin. Mutation of conserved basic residues in the C-terminal cap region of Slit D2 reduces heparin binding and abolishes biological activity. We conclude that heparin/HS is an integral component of the minimal Slit-Robo signaling complex and serves to stabilize the relatively weak Slit-Robo interaction.